2018
DOI: 10.1186/s12985-018-0980-0
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus serotypes in patients with central nervous system and respiratory infections in Viet Nam 1997–2010

Abstract: BackgroundEnteroviruses are the most common causative agents of human illness. Enteroviruses have been associated with regional and global epidemics, recently, including with severe disease (Enterovirus A71 and D68), and are of interest as emerging viruses. Here, we typed Enterovirus A-D (EV) from central nervous system (CNS) and respiratory infections in Viet Nam.MethodsData and specimens from prospective observational clinical studies conducted between 1997 and 2010 were used. Species and serotypes were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 37 publications
2
19
1
4
Order By: Relevance
“…Serotype CNS symptoms References Huang Y. et al, 2015;Mao et al, 2016;B'Krong et al, 2018;Suresh et al, 2018;Ramalho et al, 2019 EV CV-A16 E/M/AFP Goto et al, 2009;Xu et al, 2012;Huang Y. et al, 2015;Holmes et al, 2016;Suresh et al, 2018 B CV-A9 E/M/AFP Holmes et al, 2016;Chen et al, 2017;B'Krong et al, 2018;Suresh et al, 2018;Ramalho et al, 2019;Sun et al, 2019 CV-B1 E/M/AFP Holmes et al, 2016;B'Krong et al, 2018;Suresh et al, 2018;Fan and Liu, 2019;Ramalho et al, 2019;Sun et al, 2019 CV-B2 E/M/AFP Holmes et al, 2016;B'Krong et al, 2018;Suresh et al, 2018;Fan and Liu, 2019;Ramalho et al, 2019 CV-B3 E/M/AFP Holmes et al, 2016;Mao et al, 2016;Mao et al, 2018;Suresh et al, 2018;Fan and Liu, 2019;Ramalho et al, 2019;Sun et al, 2019 CV-B4 E/M/AFP Holmes et al, 2016;Mao et al, 2016;B'Krong et al, 2018;Mao et al, 2018;Suresh et al, 2018;Sun et al, 2019 CV-B5 E/M/AFP Holmes et al, 2016;Mao et al, 2016;Chen et al, 2017;…”
Section: Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Serotype CNS symptoms References Huang Y. et al, 2015;Mao et al, 2016;B'Krong et al, 2018;Suresh et al, 2018;Ramalho et al, 2019 EV CV-A16 E/M/AFP Goto et al, 2009;Xu et al, 2012;Huang Y. et al, 2015;Holmes et al, 2016;Suresh et al, 2018 B CV-A9 E/M/AFP Holmes et al, 2016;Chen et al, 2017;B'Krong et al, 2018;Suresh et al, 2018;Ramalho et al, 2019;Sun et al, 2019 CV-B1 E/M/AFP Holmes et al, 2016;B'Krong et al, 2018;Suresh et al, 2018;Fan and Liu, 2019;Ramalho et al, 2019;Sun et al, 2019 CV-B2 E/M/AFP Holmes et al, 2016;B'Krong et al, 2018;Suresh et al, 2018;Fan and Liu, 2019;Ramalho et al, 2019 CV-B3 E/M/AFP Holmes et al, 2016;Mao et al, 2016;Mao et al, 2018;Suresh et al, 2018;Fan and Liu, 2019;Ramalho et al, 2019;Sun et al, 2019 CV-B4 E/M/AFP Holmes et al, 2016;Mao et al, 2016;B'Krong et al, 2018;Mao et al, 2018;Suresh et al, 2018;Sun et al, 2019 CV-B5 E/M/AFP Holmes et al, 2016;Mao et al, 2016;Chen et al, 2017;…”
Section: Speciesmentioning
confidence: 99%
“…Non-polio enteroviruses are also known to infect the CNS and account for the majority of recent enteroviral infections with neurological disorders. Among the non-polio enteroviruses, the species Enterovirus A like enterovirus 71 (EV-A71), coxsackievirus A6 (CV-A6), and CV-A16 (Goto et al, 2009;Xu et al, 2012;Huang Y. et al, 2015;Holmes et al, 2016;B'Krong et al, 2018;Suresh et al, 2018), the species Enterovirus B like CV-B1 (Sun et al, 2019), CV-B3 (Fan and Liu, 2019), CV-B5 (Mao et al, 2018), CV-A9, Echovirus 6 (E-6), E-7, E-11, and E-13 (Holmes et al, 2016;Chen et al, 2017;B'Krong et al, 2018;Suresh et al, 2018;Chen et al, 2019;Ramalho et al, 2019;Sun et al, 2019), the species Enterovirus C like CV-A24 (Tapparel et al, 2013;B'Krong et al, 2018;Suresh et al, 2018), and the species Enterovirus D like EV-D68 (Tapparel et al, 2013;Messacar et al, 2018) have been shown to involve the CNS and cause diverse neurological complications such as encephalitis, meningitis and acute flaccid paralysis (AFP) (Tapparel et al, 2013) (see Table 1 for details).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Алгоритм молекулярно-генетических и вирусологических исследований, проводимых при выявлении энтеровирусов у больных с клиникой HFMD и идентификации типа/генотипа вируса, представлен на рисунке 2. В то же время в ряде научных публикаций представлены результаты исследований по детекции энтеровирусов у больных с респираторными заболеваниями и нейроинфекциями [7,10,11,20,30,32].…”
Section: заболеваемость энтеровирусной инфекцией в социалистической рunclassified
“…Both herpangina and HFMD are highly contagious infections, usually self-limiting but rarely may cause serious cardiac and neurological complications [8]. Humans are the only natural host of these viruses [9]. It is therefore both HFMD and herpangina need to be sought in the history of patients presented with onychomadesis.…”
Section: Introductionmentioning
confidence: 99%